The Energy Community and the Grid - Axel Gautier; Julien Jacqmin; Jean-Christophe Poudou (Center for Economic Studies and ifo Institute (CESifo), 2023)
Renewable energy communities involve various agents who decide to jointly invest in renewable production units and storage. This paper examines how these communities interact with the energy system and can decrease its overall cost. First, we show that a renewable energy community can contribute positively to welfare if the electricity produced by the investment is consumed close to its place of production, i.e. if the community has a high degree of self-consumption. Second, our analysis identifies the condition on prices and grid tariffs to align the community's interest with welfare maximization. We also show that some of these grid tariffs do not have a negative impact on non-members of the community and could therefore limit potential distributional issues. Third, we argue that various internal organization of the renewable energy communities are feasible. The internal organization impacts the distribution of benefits among members but not the global efficiency of the community.
Keywords: L30; L94; Q48; 330; energy communities; decentralized production unites; energy transition; grid regulation